2017
DOI: 10.1186/s12884-017-1318-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a quality improvement intervention for obstetric and neonatal care in selected public health facilities across six states of India

Abstract: BackgroundWhile increase in the number of women delivering in health facilities has been rapid, the quality of obstetric and neonatal care continues to be poor in India, contributing to high maternal and neonatal mortality.MethodsThe USAID ASSIST Project supported health workers in 125 public health facilities (delivering approximately 180,000 babies per year) across six states to use quality improvement (QI) approaches to provide better care to women and babies before, during and immediately after delivery. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 19 publications
(15 reference statements)
1
10
0
Order By: Relevance
“…All women were allowed to have at least one female companion along with the CHW throughout labour and delivery. Several studies have highlighted women experiencing abandonment and neglect during childbirth [ 29 , 61 , 62 ]. Our study also found that some women were left unattended in the delivery room after childbirth for more than 15 minutes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All women were allowed to have at least one female companion along with the CHW throughout labour and delivery. Several studies have highlighted women experiencing abandonment and neglect during childbirth [ 29 , 61 , 62 ]. Our study also found that some women were left unattended in the delivery room after childbirth for more than 15 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…Training and orientation of staff towards aspects of person-centred care including respectful & supportive care; information sharing; effective communication skills and patient privacy can go a long way in sensitizing providers around person-centred care, supported by public display of behavioural norms in the charter of patient rights and entitlements. The findings from a quality improvement (QI) intervention in public health facilities across six states of India, suggest that simple QI methods like redesign of space and task shifting have the potential to improve quality of facility-based routine clinical practices in resource poor settings like India [ 62 ] QI cycles may be followed by performance based grading of facilities on attainment of specific quality benchmarks to encourage adoption of good care practices. A concept of ‘positive deviance approach’ may also be introduced for collating and sharing ‘best practices’ with regards to quality of care in facilities performing better while having access to the same resources and facing similar or worse challenges.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maternal health providers in Bihar and other states in India have identified the availability of adequate health infrastructure, functioning HMIS and evidence-based training with supportive supervision as enablers of quality in maternal health service provision 30 34. However, intervention studies on improving nurse providers skills and practices have used varied modes of training and duration, with some studies noting significant improvements in adherence to evidence-based practices and reduction in harmful practices like labour augmentation, episiotomy for primigravida and application of fundal pressure 35–38. Studies reported mixed results on other practices, such as position of mother during delivery, the use of partograph and hand-washing 36.…”
Section: Introductionmentioning
confidence: 99%
“…These methods have also been found to be effective in India. 28 , 29 Based on our experience of using the F-BNA tool to identify problems and QI methods to address these problems, we propose that this methodology can help in the identification of health system bottlenecks at the facility level, their prioritisation, and improvement in these key areas. This methodology is of prime importance in low- and middle-income countries (LMICs) where resource constraints are a constant problem.…”
Section: Discussionmentioning
confidence: 99%